Municipal development in the differentiated mesoregions of the western Amazon (Gestão & Regionalidade, 2022)
This paper analyzes the attractiveness and disparity in the socioeconomic development of the municipalities that comprise the Alto do Solimões and Rio Acre Valley Differentiated Regions, both located in the western area of the Brazilian Amazon. The methodology used was the estimation of the centrality and regional disparity indexes based on population, growth and socioeconomic development data. The results showed that the municipalities have improved their human development indicators but have not yet managed to advance in employment and income. The convergence of socioeconomic indicators was positive, but the centrality of central municipalities remains very significant.